Getting to the heart of the matter: investigating the idiopathic sudden cardiac death of a previous well soldier. Issue 5 (17th March 2019) - Eveson, Leanne Jane; Cox, A T; Dhutia, H; Ensem, B; Behr, E; Sharma, S
Abstract : A 25-year-old infantry soldier, who was previously fit and well, had a cardiac arrest while undertaking an advanced fitness test. Despite early cardiopulmonary resuscitation by colleagues and the emergency services, he was later pronounced dead. A postmortem performed by an expert pathologist and a toxicology screen were normal and the death was attributed to sudden arrhythmic death syndrome (SADS). Screening of his family in our Inherited Cardiac Conditions clinic identified Brugada syndrome (BrS) in two first-degree relatives. This case generates discussion on sudden cardiac death, family screening in SADS, BrS and the limitations of recruit screening with an ECG.